GIGANTEA – an emerging story - Mishra, Priyanka; Panigrahi, Kishore C. (Frontiers in Plant Science, 2015)
GIGANTEA (GI) is a plant specific nuclear protein and functions in diverse physiological processes such as flowering time regulation, light signaling, hypocotyl elongation, control of circadian rhythm, sucrose signaling, starch accumulation, chlorophyll accumulation, transpiration, herbicide tolerance, cold tolerance, drought tolerance and miRNA processing. It has been five decades since its discovery but the biochemical function of GI and its different domains are still unclear. Although it is known that both GI transcript and GI protein are clock controlled, the regulation of its abundance and functions at the molecular level are still some of the unexplored areas of intensive research. Since GI has many important pleotropic functions as described above scattered through literature, it is worthwhile and about time to encapsulate the available information in a concise review. Therefore, in this review, we are making an attempt to summarize (i) the various interconnected roles that GI possibly plays in the fine-tuning of plant development, and (ii) the known mutations of GI that have been instrumental in understanding its role in distinct physiological processes.